2017
DOI: 10.1016/j.virol.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of infectivity, immunogenicity and cross-protective efficacy of live attenuated influenza vaccines containing nucleoprotein from cold-adapted or wild-type influenza virus in a mouse model

Abstract: This study sought to improve an existing live attenuated influenza vaccine (LAIV) by including nucleoprotein (NP) from wild-type virus rather than master donor virus (MDV). H7N9 LAIV reassortants with 6:2 (NP from MDV) and 5:3 (NP from wild-type virus) genome compositions were compared with regard to their growth characteristics, induction of humoral and cellular immune responses in mice, and ability to protect mice against homologous and heterologous challenge viruses. Although, in general, the 6:2 reassortan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The rationale for including recent NP in the LAIV genome composition has been discussed in the context of our previous studies in a mouse model [37,38], and in in vitro study of human donor peripheral blood mononuclear cells [36]. In this ferret study, for the first time the two strategies for enhancing the cross-protective potential of traditional LAIVs were combined, and sequential immunizations with the vaccines expressing cHAs and WT NP were compared with classical LAIVs and with cHA-based…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for including recent NP in the LAIV genome composition has been discussed in the context of our previous studies in a mouse model [37,38], and in in vitro study of human donor peripheral blood mononuclear cells [36]. In this ferret study, for the first time the two strategies for enhancing the cross-protective potential of traditional LAIVs were combined, and sequential immunizations with the vaccines expressing cHAs and WT NP were compared with classical LAIVs and with cHA-based…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only one third of the predicted the human leukocyte antigen (HLA) class I-restricted NP epitopes identified in A(H2N2) MDV Len/17 are conserved in recent A(H1N1) and A(H3N2) isolates (Machkovech et al, 2015). Additionally, we have found that at least 28 HLA class I-restricted epitopes have diverged between Len/17 MDV and recent A(H3N2) influenza virus NP (Isakova-Sivak et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, all three vaccines fully protected immunized mice against replications in the respiratory tract of the homologous challenge virus administered at a high dose (100 MLD 50 ), whereas this challenge virus reproduced to high titer levels in mock-immunized mice, both in the lungs and the nasal turbinates ( Figure 5 C). Although we did not measure mucosal IgA antibody levels in immunized mice, our previous results indicate that this arm of adaptive immune responses may also contribute to the protection [ 49 ]. Overall, these data suggest that the inserted immunogenic epitopes of AdV did not interfere with influenza-specific antibody immune responses induced by LAIV intranasal immunization.…”
Section: Resultsmentioning
confidence: 99%